MEDAN MAKNA ALAT RUMAH TANGGA DARI TANAH LIAT DAN BATU PADA MASYARAKAT KAILI - M. Asri B. (Multilingual, 2015)
Abstract This paper is about the description of semantic field of housewares made from clayand stone in Kaili society. The method used in this research was descriptive withrecording and interviewing method. The analysis was processing by grouping,classifying the similar and dissimilar data and classifying the similar but differentdata into another group. The data were analysing into seventeen houseware’svocabularies based on the material and function. Based on the material, there are clayand stone houseware. Based on the function, it can be use as (1) grilling and cookingplace (2) saving, placing (3) grinding, milling (4) illuminating, (5) heating andgrilling, (6) protecting, and (7) sharpening.